Gravity, geoid and space missions GGSM 2004, IAG International Symposium, Porto, Portugal, August 30-September 3, 2004 - IAG International Symposium on Gravity, Geoid, and Space Missions (International Association of Geodesy symposia, 2005)
The lAG International Symposium on Gravity, Geoid, and Space Missions 2004 (GGSM2004) was lield in the beautiful city of Porto, Portugal, from 30 August to 3 September 2004. This symposium encompassed the themes of Commission 2 (Gravity Field) of the newly structured lAG, as well as interdisciplinary topics related to geoid and gravity modeling, with special attention given to the current and planned gravi- dedicated satellite missions. The symposium also followed in the tradition of mid-term meetings that were held between the quadrennial joint meetings of the International Geoid and Gravity Commissions. The previous mid-term meetings were the International Symposia on Gravity, Geoid, and Marine Geodesy (Tokyo, 1996), and Gravity, Geoid, and Geodynamics (Banff, 2000). GGSM2004 aimed to bring together scientists from different areas in the geosciences, working with gravity and geoid related problems, both from the theoretical and practical points of view. Topics of interest included the integration of heterogeneous data and contributions from satellite and airborne techniques to the study of the spatial and temporal variations of the gravity field. In addition to the special focus on the CHAMP, GRACE, and GOCE satellite missions, attention was also directed toward projects addressing topographic and ice field mapping using SAR, LIDAR, and laser altimetry, as well as missions and studies related to planetary geodesy. Initial results from retracking and reprocessing the ERS-1 geodetic mission altimetry for gravity field purposes -- Evaluation of airborne gravimetry integrating GNSS and strapdown INS observations -- Status of the european gravity and Geoid Project EGGP.-photon counting airborne laser swath mapping (PC-ALSM) -- A comparison of different isostatic models applied to satellite gravity gradiometry -- Spectral analysis of mean dynamic ocean topography from the GRACE GGM01 geoid -- Results of the International Comparison of Absolute Gravimeters in Walferdange (Luxembourg) of November 2003 -- Decadal ocean bottom pressure variability and its associated gravitational effects in a coupled ocean-atmosphere model.